2023
DOI: 10.1038/s41598-022-27328-y
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection augments species- and age-specific predispositions in cotton rats

Abstract: Heterogeneity of COVID-19 manifestations in human population is vast, for reasons unknown. Cotton rats are a clinically relevant small animal model of human respiratory viral infections. Here, we demonstrate for the first time that SARS-CoV-2 infection in cotton rats affects multiple organs and systems, targeting species- and age-specific biological processes. Infection of S. fulviventer, which developed a neutralizing antibody response and were more susceptible to SARS-CoV-2 replication in the upper respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…They usually experience physical and cognitive impairments, chronic immune activation and multimorbidity even without COVID-19 at ages younger than HIV-1 negative people [ 125 , 126 , 127 , 128 , 129 ]. Thus, aging and age-associated comorbidity make PLWH succumb to SARS-CoV-2 infection and COVID-19 severity [ 130 ]. Since COVID-19 also causes neurological syndromes, SARS-CoV-2 may imply a cumulative effect on preexisting HAND or may lead to the development of HAND.…”
Section: Impact Of Covid-19 On Plwhmentioning
confidence: 99%
See 1 more Smart Citation
“…They usually experience physical and cognitive impairments, chronic immune activation and multimorbidity even without COVID-19 at ages younger than HIV-1 negative people [ 125 , 126 , 127 , 128 , 129 ]. Thus, aging and age-associated comorbidity make PLWH succumb to SARS-CoV-2 infection and COVID-19 severity [ 130 ]. Since COVID-19 also causes neurological syndromes, SARS-CoV-2 may imply a cumulative effect on preexisting HAND or may lead to the development of HAND.…”
Section: Impact Of Covid-19 On Plwhmentioning
confidence: 99%
“…Several cohort studies on PLWH have demonstrated that PLWH are among the high-risk group for contracting SARS-CoV-2 infection [16,[178][179][180]. PLWH are more likely to be infected with SARS-CoV-2 due to immunocompromised status owing to HIV-1 infection-induced dysregulated immune response/immune suppression and underlying comorbidities [130,181]. Moreover, there was complex immune dysregulation observed with higher levels of IFNα/β and T-cell activation in coinfected people than in healthy controls [182,183].…”
Section: Sars-cov-2 Infection and Covid-19 Severity In Plwhmentioning
confidence: 99%